A Study of Maltreated Children and Their Families in Juvenile Court. III. Case Plans. (June 2014) - Karatekin, Canan; Gehrman, Richard; Lawler, Jamie
Abstract: We reviewed publicly available court records of 88 cases referred to juvenile court for maltreatment in Hennepin County, Minnesota. The goal of the current study was to examine the content of, and extent of compliance with, case plans. There was an average of 9.5 items per child on the case plan. About half the case plans did not address at least one presenting maltreatment type. Compliance was generally high for items ordered for the children, and for cases that ended in family preservation. However, information on compliance was not included in the court records for many of the items.